THE INFLUENCE OF ULTRASOUND CAVITATION ON VAGINAL MICROBIOCENOSIS IN THE PATHOLOGY OF RECURRENT INFLAMMATION OF THE GENITALIA IN WOMEN - Kodirova , Z.N.; Kattakhodzhaeva, M.H. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
One of the most frequent complaints in the practice of a gynecologist has been and remains pathological discharge from the vagina. In 61-87% of cases, the discharge is a symptom of bacterial vaginosis, an infectious noninflammatory syndrome characterized by a violation of the vaginal microbiocenosis. According to various sources, among all vulvovaginal infections, the proportion of bacterial vaginosis ranges from 12 to 80%. We conducted a study of the microbiocenosis of the vagina of women with recurrent colpitis before treatment and in two groups after treatment. In the treatment of the main group, the method of ultrasonic cavitation was applied. In the comparison group, local therapy accepted in national standards for 6 days of vaginal Clindox capsules containing Clindamycin phosphate, Clotrimazole and Tinidazole was used. The results of the study after both types of treatment indicate a significant improvement in the microbial landscape of those studied after the treatment. After a 6-day course of treatment, microbiological studies were repeated using the Femoflor 16 method.